Cats with Inflammatory Bowel Disease and Intestinal Small Cell Lymphoma Have Low Serum Concentrations of 25‐Hydroxyvitamin D. (16th January 2014) - Lalor, S.; Schwartz, A.M.; Titmarsh, H.; Reed, N.; Tasker, S.; Boland, L.; Berry, J.; Gunn‐Moore, D.; Mellanby, R.J.
<x xml:space="preserve">Abstract</x> Background Inflammatory bowel disease (IBD) and intestinal small cell lymphoma (ISCL) are common diseases in cats. The prevalence of alterations in the serum concentrations of fat soluble vitamins, such as vitamin D, in cats with IBD and ISCL is unknown. Hypothesis/Objectives The objective of this study was to measure serum 25 hydroxyvitamin D (25[OH]D) concentrations in cats with IBD or ISCL. Serum 25(OH)D also was measured in healthy cats, and in hospitalized ill cats with nongastrointestinal diseases. Animals Eighty‐four cats were included in the study: 23 in the healthy group, 41 in the hospitalized ill group, and 20 in the IBD/ISCL group. Methods Retrospective study. Serum samples for vitamin D analysis were frozen at −20°C until serum 25(OH)D was measured by high‐performance liquid chromatography (HPLC). Results Although there was overlap in serum 25(OH)D concentrations among the 3 groups, serum 25(OH)D concentrations were significantly lower in the cats with IBD or ISCL compared to healthy cats (P < .0001) and hospitalized ill cats (P = .014). In the IBD/ISCL group, there was a significant moderate positive correlation between serum albumin and 25(OH)D concentrations (r = 0.58, P = .018). Conclusion and Clinical Importance The median serum concentration of 25(OH)D was significantly lower in cats with IBD/ISCL than in healthy cats and in hospitalized ill cats. Additional studies are required to elucidate the mechanism of hypovitaminosis D in cats with gastrointestinal diseases, to define the best management strategy to treat this complication, and to investigate its potential prognostic implications.